Impact of Conflict and Stress Management on Employee Performance in Indonesia’s Textile Industry - Samsudin, Acep; Ikaningtyas, Maharani; Rintalla, Maulidya (Business Review and Case Studies, 2024)
Background: The Indonesian textile industry, known for its high competition and labor intensity, presents a unique environment to study the impact of work conflict and stress on employee performance, particularly within its production departments. Purpose: This study aims to examine how work conflict and stress affect the performance of employees in the production department of the Indonesian textile industry. Design/methodology/approach: A quantitative research approach was employed, utilizing descriptive and associative methods. Data was gathered from a purposive sample of 192 employees to ensure representativeness. The data analysis involved multiple linear regression, coefficient of determination, multiple correlation coefficient, and partial tests (T-test). Findings/Result: The analysis revealed that work conflict and stress significantly impact employee performance, accounting for 51% of the variance. A strong correlation (R = 0.714) was identified, indicating that higher levels of work conflict and stress are associated with lower employee performance. The study also noted that 49% of the variance in performance is due to factors not explored in this research, suggesting areas for future studies. Conclusion: The findings highlight the substantial influence of work conflict and stress on employee performance. Effective management strategies to address these issues are crucial for enhancing employee efficiency and overall organizational productivity. Originality/value (State of the art): This study contributes to existing knowledge by analyzing the relationship between work conflict, stress, and employee performance in a competitive, labor-intensive industry. Keywords: employee performance, indonesia, stress, textile Industry, work conflict